Dissemination of nutrition and healthy diet in the era of the COVID-19 pandemic - Dhian Kartikasari; Lucky Radita Alma; Septa Katmawanti; Nurnaningsih Herya Ulfah; Indana Tri Rahmawati; Nugraheni Puji Lestari; Endah Retnani Wismaningsih (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The purpose of this community service was to increase knowledge about healthy diet arrangements for female students during the new normal period.  A total of 21 female students participated in the socialization of balanced nutrition during the pandemic.  Nutrition outreach activities were carried out in the form of online webinars through zoom cloud meetings.  Before and after outreach activities, the measurement of knowledge before and after the intervention (2 times the measurement of post-intervention).  The research instrument used was a questionnaire in the google form.  From the results of this community service, it was found that the nutrition dissemination activities carried out had an impact in the form of increasing nutritional knowledge, especially related to balanced nutrition guidelines during the pandemic.  This shows that the subject's knowledge was increasing and the subject understands about nutrition education.  The most noticeable increase in knowledge was about the largest portion in balanced nutrition.  There was a difference between the results of the pre-test, post-test 1, and post-test 2.